DEVELOPMENT OF CURRICULUM ENHANCEMENT OF TEACHER COMPETENCY IN LEARNING MANAGEMENT FOR ENGLISH LISTENING AND SPEAKING SKILLS INTEGRATING ASEAN CONTENT UNDER ROI ET PROVINCIAL EDUCATION OFFICE - Sangkhaphan, Suthat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research aims were to 1) study the problems and needs of developing a curriculum to enhance teacher competency in learning management for English listening and speaking skills integrating with ASEAN content under Roi Et Provincial Education Office 2) design and develop a curriculum to enhance teacher competency in learning for listening and speaking English skills integrating ASEAN content under Roi Et Provincial Education Office 3) study the results of using the curriculum to enhance teacher competency in learning management for listening and speaking English skills integrating with ASEAN content 4) study the results of the assessment of teacher competency courses in learning management for listening and speaking English skills integrating ASEAN content under Roi Et Provincial Education Office. The research was conducted the research and development framework, totaling 4 phases, 7 participants, acquired by the and 172 students in Mathayomsuksa 3 whose development teachers were responsible for English language learning in 2018 academic year. The research instruments were questionnaires and assessment forms. The statistics used to analyze the data were percentage, mean, standard deviation; hypothesis testing with t-test (dependent samples) and content analysis The results of the research were found that; 1. The results of the study of the present condition Problems and needs in developing teachers' learning management competency found that the current state of teacher competency in learning management skills in listening and speaking English integrating ASEAN content, as overall the quality level was moderate. 2. The results of the development of the curriculum for enhancing teacher competency in managing learning in listening and speaking English skills integrating ASEAN content under Roi Et Provincial Education Office found that the curriculum for enhancing teacher competency consisted of 5 components: the curriculum principles; course aims course content teacher empowerment process and the measurement and evaluation of the course. 3. The results of using the curriculum to enhance teacher competency in learning management of listening and speaking English skills integrating ASEAN content under Roi Et Provincial Education Office can be summarized as follows: The training was statistically significant at the .05 level. 4. The evaluation of the curriculum for enhancing teacher competency in learning management of listening and speaking English skills integrating ASEAN content through CIPP model was used to evaluate 4 aspects. The results of the suitability assessment were at a high level.